The Arthur of the Low Countries : the Arthurian legend in Dutch and Flemish literature - Besamusca, Bart; Brandsma, Frank (Arthurian literature in the Middle Ages., 2021)
This book provides a comprehensive and informed survey of Arthurian literature in Dutch, aimed at readers who want to learn about the Arthurian tradition as it took shape in a language and culture with which they are not yet familiar.